Optimization and synthesis of an 18F‐labeled dopamine D3 receptor ligand using [18F]fluorophenylazocarboxylic tert‐butylester. (28th December 2015) - Nebel, Natascha; Maschauer, Simone; Hocke, Carsten; Hübner, Harald; Gmeiner, Peter; Prante, Olaf
Abstract : There is still no efficient fluorine‐18‐labeled dopamine D3 subtype selective receptor ligand for studies with positron emission tomography. We aim at improving the D3 selectivity and hydrophilicity of a candidate ligand by changing the substitution pattern to a 2, 3‐dichlorophenylpiperazine and hydroxylation of the butyl chain. The compound [ 18 F]3 exhibited D3 affinity of Ki  = 3.6 nM, increased subtype selectivity (Ki (D2 /D3 ) = 60), and low affinity to 5‐HT1A and α1 receptors (Ki (5‐HT1A /D3 )  = 34; Ki (α1 /D3 ) = 100). The two‐step radiosynthesis was optimized for analog [ 18 F]4 by reducing the necessary concentration of the precursor amine (57 mM), which reacted with [ 18 F]fluorophenylazocarboxylic tert ‐butylester under basic conditions. The optimization of the base (Cs2 CO3, 23 mM) and the adjustment of reaction temperature led to the radiochemical yield of 63% after 5 min at 35°C. The optimized reaction conditions were transferred on to the synthesis of [ 18 F]3 with an overall non‐decay corrected yield of 8‐12% in a specific activity of 32‐102 GBq/µmol after a total synthesis time of 30‐35 min. This provides a D3 radioligand candidate with improved attributes concerning selectivity and radiosynthesis for further preclinical studies. Abstract : The optimized reaction of [ 18 F]fluorophenylazocarboxylic tert‐butylester with an amine was applied to the radiosynthesis of[ 18 F]3, achieving an overall non‐decay corrected radiochemical yield of 8–12% and a specific activity of 32–102 GBq/μmol after a total synthesis time of 35 min. The hydroxylated phenylazacarboxamide[ 18 F]3 showed nanomolar affinity for the dopamine D3 receptor and a subtype selectivity of > 6‐fold, providing a D3 radioligand candidate with improved attributes and a reliable and easy radiosynthesis to facilitate further preclinical studies.